Kapitaalvorming by landboukoöperasies - W. D. Hamman; I. J. Lambrechts; F. J. Mostert (South African Journal of Business Management, 1988)
– This article covers an analysis of capital formation of 31 representative agricultural cooperatives and follows on a previous article which covered their financial situation for the period 1975 - 1985. Concerning the capital formation, it appears that share capital did not play a major part as a source of permanent capital. Although reserves increased, it could not keep pace with the increase of the total assets. The main sources of capital formation were deferred bonuses and members' levy funds which increased more rapidly than the total assets. The total interest credited and paid on the deferred bonuses and members' levy funds were respectively 7% and 9% of the opening balances. The planned rotation of both kinds of funds was relatively small in comparison with the opening balances, while the unplanned payment of the members' levy funds was larger than the planned rotation. Although rotation did not take place to a large extent, it can be a matter of concern when the funds will have to be repaid in the foreseeable future.
Keywords: 650